Low gastrointestinal bleeding due to a pancreatic tumor. Selective angiography and embolization treatment - Pereyra Borrelli, César; Boschi Pau, Jorge; Tiscornia, Eduardo (Cirugía del Uruguay, 1983)
. The case of a patient with an important digestive bleeding (melena) is presented. The patient had a pancreatic tumor that eight years ago couldn't be resected or biopsel lue to easy bleeling anl invasion of neighbor organs.